2020
DOI: 10.1016/j.nbscr.2020.100054
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin's dual-effect on the circadian clock triggers proliferation and apoptosis

Abstract: The circadian clock, which generates the internal daily rhythm largely mediated through release of melatonin, can be disrupted in various ways. Multiple factors result in a disruption of the circadian cycle in the clinical context, of interest are anti-cancer drugs such as cisplatin. Cisplatin modulates the circadian clock through two mechanisms: 1) the circadian clock control of DNA excision repair and 2) the effect of circadian clock disruption on apoptosis. Cisplatin can stimulate multiple classified molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…58 Additionally, Ca 2+ and melatonin have also been implicated in the regulation of hepatocyte apoptosis. 59 The CRY mutation activates p53-independent apoptotic pathways in hepatocytes, while the CLOCK gene and neuronal PAS domain protein 2 gene, NPAS2, promote cell proliferation and inhibit mitochondrial apoptosis. 60 While there has been extensive research on the CRs of hepatocytes in animals, 61 there are still several unclear aspects regarding the structure of these rhythms.…”
Section: Discussionmentioning
confidence: 99%
“…58 Additionally, Ca 2+ and melatonin have also been implicated in the regulation of hepatocyte apoptosis. 59 The CRY mutation activates p53-independent apoptotic pathways in hepatocytes, while the CLOCK gene and neuronal PAS domain protein 2 gene, NPAS2, promote cell proliferation and inhibit mitochondrial apoptosis. 60 While there has been extensive research on the CRs of hepatocytes in animals, 61 there are still several unclear aspects regarding the structure of these rhythms.…”
Section: Discussionmentioning
confidence: 99%
“…e growth and diffusion of cancer cells depend on angiogenesis and tumor neogenesis, which is the most important antitumor method of vascular targeted therapy [19,20]. In some studies, NSCLC patients were divided into 34 cases of platinum chemotherapy and 54 cases of platinum plus recombinant human endostatin [21][22][23]. It was found that the progression-free survival rate and overall survival rate of patients treated with combination therapy were significantly improved.…”
Section: Discussionmentioning
confidence: 99%
“…Combination chemotherapy provides good outcomes initially in impairing tumor growth, but it ultimately fails as cancer cells develop therapeutic resistance ( 87 ). Cisplatin is a first-line chemotherapy treatment that directly interacts with the circadian clock proteins and enhances the body’s natural response to cancerous cells ( 88 ). It upregulates CLOCK and BMAL1, resulting in increased proliferation and increased apoptosis, respectively ( 88 ).…”
Section: Crds and Gu Cancersmentioning
confidence: 99%
“…Cisplatin is a first-line chemotherapy treatment that directly interacts with the circadian clock proteins and enhances the body’s natural response to cancerous cells ( 88 ). It upregulates CLOCK and BMAL1, resulting in increased proliferation and increased apoptosis, respectively ( 88 ). In bladder cancer tissue from human specimens, BMAL1 was downregulated, and CLOCK was upregulated, so cisplatin acts differently on both proteins through unclear mechanisms ( 89 ).…”
Section: Crds and Gu Cancersmentioning
confidence: 99%
See 1 more Smart Citation